Effect of different supplementations on growth and yield of oyster mushroom - Mistry, Sneha jayanitibhai; Parmar, R.G. (Mushroom Research, 2024)
Addition of organic and inorganic supplements to the substrate during cultivation is little known to influence the yield of various species of oyster mushroom. Therefore, an experiment with brans, flours and haulm as organic supplements in cultivation of oyster mushroom was undertaken in order to find out better and cheaper supplements to increase the yield of oyster mushroom. The paddy straw+ 2% groundnut haulm took minimum incubation period of 15.83 days. Further paddy straw+ 2% rice husk (17 days), paddy straw+ 2% chickpea haulm (17.33 days) and treatment paddy straw+ 2% wheat bran (18.50 days). The number of days required for pinhead formation differed significantly and varied between 6.67 to 11.67 days after pinhead formation. Similarly, the days required for the first, second and third harvest ranged from 24.33 to 58.83 days for the total three harvesting. The number of fruiting bodies per bags varied from 58 to 72.33 due to different treatments. The paddy straw+ 2% chickpea haulm produced significantly higher number of fruiting bodies per bag (72.33) while the minimum numbers of fruiting bodies were found in the treatment paddy straw+ 2% bajra flour (58.00) fruits / bag. A significant variation in average fruit body weight (8.13 to 12.05 g per fruit), pileus diameter (4.13 to 6.98 cm), stipe length (2.60 to 4.21 cm) and stipe size (2.43 to 3.54 cm) were noted due to different treatments. The observations on yield performance due to different treatments revealed that treatment with paddy straw+ 2% groundnut haulm recorded significantly maximum yield (871 g/kg dry substrate) of mushroom substrate which was at par with treatment, paddy straw+ 2% chickpea haulm (844 g/kg dry substrate), paddy straw+ 2% rice husk (831g/kg dry substrate) and, paddy straw+ 2% wheat bran (790 g/kg dry substrate). The treatment of paddy straw+ 2% groundnut haulm registered the highest (1:59) BCR followed by paddy straw+ 2% chickpea haulm (1.54), paddy straw+ 2% rice husk(1:52) and paddy straw+ 2% wheat bran (1:43).